Opening the Implicit Leadership Theories’ Black Box: An Experimental Approach with Conjoint Analysis - Tavares, Gustavo M.; Sobral, Filipe; Goldszmidt, Rafael; Araújo, Felipe (Frontiers in Psychology, 2018)
Although research on Implicit Leadership Theories (ILTs) has concentrated on determining which attributes define a leadership prototype, little attention has been paid to testing the relative importance of each of these attributes for individuals’ leadership perceptions. Building on socio-cognitive theories of impression processes, we experimentally explore the formation of leadership perceptions based on the recognition of 6 key attributes in a series of 3 experimental studies comprising 566 US-based participants recruited online via Amazon Mechanical Turk. Our results show that while certain attributes play an important role in the leader categorization process, others are less relevant. We also demonstrate that some attributes’ importance is contingent on the presence of other attributes and on the leadership schema type activated in respondents’ minds. Consistent with the Leadership Categorization Theory, our findings support the premise that individuals cognitively hold a superordinate leadership prototype, which imposes constraints on their more basic level prototypes. We discuss the implications of these results for leadership theory and practice.